Optimization of sowing rates and mineral nutrition in winter barley cultivation under climatic risks in the Left-Bank Forest-Steppe of Ukraine - Mukha, B. (Scientific Progress & Innovations, 2025)
The purpose of this review is to summarize scientific approaches and experimental findings related to the optimization of sowing rates and mineral nutrition in winter barley (Hordeum vulgare L.) cultivation under the agroecological conditions of the Left-Bank Forest-Steppe of Ukraine, considering current climatic challenges. The economic significance of winter barley is substantiated by its high yield potential compared to spring barley and earlier maturation (by 10–16 days), which allows for more efficient use of land for successive crops. An analysis of sowing area dynamics during 2019–2024 reveals a spatial shift in cultivation from the traditional southern regions (due to military actions) toward the northern and western parts of Ukraine, where relatively stable moisture availability is observed. Optimal sowing rates are determined to range between 3.5 and 5.5 million viable seeds per hectare, depending on the variety, sowing date, and moisture conditions. Mineral nutrition is identified as a key factor in productivity enhancement; in particular, localized nitrogen application (N₃₀–N₉₀) during the tillering stage significantly increases grain protein content. In different agroclimatic zones, effective fertilization strategies vary within the range of N₃₀P₃₀K₃₀ to N₁₂₉P₆₆K₁₃₂. Climatic transformations in the Left-Bank Forest-Steppe demonstrate a marked trend toward aridization: the average annual temperature has increased by 1.1 °C, annual precipitation has decreased by 5 %, and the frequency of drought conditions has risen from 47 % to 61 %. Simultaneously, the probability of optimal water availability has nearly halved. Based on the findings, several technological recommendations are proposed: adjustment of sowing rates depending on sowing dates (3.2–4.0 million seeds/ha for early sowing and 4.5–5.0 million for later sowing); staged nitrogen application; localized phosphorus-potassium fertilization; use of anti-stress microfertilizers; implementation of digital technologies; and the adoption of high-yielding, stress-tolerant varieties.